KAJIAN KEBUTUHAN PERLINTASAN TIDAK SEBIDANG JALUR KERETA API DENGAN JALAN RAYA DI TITIK PERLINTASAN GANEFO KECAMATAN MRANGGEN - Bambang Sudarmanto (Universitas Semarang, 2018)
The crossing railway line with the highway is quite a lot in several places in Indonesia, especially on the island of Java. This is a problem in itself because it considers this crossing to have a negative impact on users of land transportation. Moreover, the government does not yet have a policy relating to planning, regulation, supervision and supervision at a level crossing and is discussed with traffic accidents at the intersection of a basic plot to develop systems and procedures at level crossings.The crossing between the Semarang-Purwodadi highway and the Semarang-Surabaya / Solo railway line across the crossing lane on Ganefo still uses a level crossing. In the end, it caused a quite serious problem, namely severe congestion at the time of leaving and returning to work and even frequent traffic accidents. The existence of level crossings at this point is the focus of research by using proposals issued by the Ministry of Attention regarding railway crossings with highways can be made without a door, or can be in a plot with doors equipped, or can be made a plot, according to the research objectives. this is knowing the type of crossing that is right at the crossing of Ganefo. The results of the calculation of the Daily Average Daily Traffic of the Purwodadi-Semarang Directions traffic on the Ganefo pathway found numbers of 15928.2 pcu with the percentage of motorcycle transportation modes (motor cycle) amounting to 87.47%. Whereas the opposite direction, namely Semarang-Purwodadi, is 12784.8 pcu and the percentage of motorbikes is 78.85% of the total traffic volume. The direct observation of the train journey at the Ganefo crossing point shows the number of train trips that cross the Ganefo as many as 18 trains / day. The average length of the vehicle is at 191,429 meters during peak hours. Charting the criteria for selecting the crossing type of the Ministry of Transportation shows that the crossing point of Ganefo still depends on the position of the point where it is still permitted to use level crossings with safety doors. However, taking into account the increasing number of train trips and considerations of inconvenience and security of road users, this is at risk because depending on the position of the point required the type of crossing is not as large.